Impact of air pollution on the mitotic activity in meristematic cells in shallot (Allium cepa L. var. ascalonicum) - Erika Glaseničnik; Dieter Gril; Maria Muller; Cvetka Ribarič-Lasnik; Franc Batič (Acta Biologica Slovenica, 2003)
Test shallot plants Allium cepa L. var. ascalonicum were exposed to field conditions in research plots in the most polluted areas in Slovenia in the vegetation season in 1999. The intention of this research was to evaluate the influence of air pollution on mitotic activity in meristematictissues of root tips of bioindication plants. At each sampling site the mitotic activity was determined under field conditions and in a pot experiment. The maturated bulbs were collected from the field and after winter dormancies cytogenetic analyses were run on them in a lab. Root tips were fixed in Clark's fixative and afterwards stained with Schiff's reagent. Significant differences in the mitotic activity in different sampling plots in pot experiments were found. The results showed the presence ofcytotoxic substances at chosen sampling sites which caused the decrease of mitotic cell division.